(untitled) (Journal of the College of Education for Women, 2019)
1-Alglul is the introduction of after prize or (Booty) secretly before it is divided, and the general sense is an absolute betrayal, and God has forbidden and the Prophet (Peace be upon him) by Muslims; such as bribery and gift-giving and other function by the terminology.2-The signals and texts Alglul in the Covenant Rashidi and the Umayyad and Abbasid very few, compared to the Covenant of the Prophet, and so by the Quranic verses that were deprived Alglul and other Transmitting booty for the Muslims, and the hadith which magnified Alglul and showed its consequences in this life and the afterlife, and the tutelage of the Prophet (Peace be upon him) its active role in reducing Alglul, it was the great commandments included notification and warning and stay away from Alglul all its forms, because it is a major sin.3- Caliphs dish in the Covenant Rashidi and the Umayyad and Abbasid Apostle approach (Peace be upon him) approach has included directing the commandments of the leaders of the army and the armies not to attack the spoils any common funds, that malignant; and not oppression of slaves, and must Gallic accountable and punished, according to the Koran and the Sunnah of the Prophet (Peace be upon him).4-The Caliphs and the Umayyad and Abbasid (God bless them), Athlon piety and caution Alglul was monitoring and accounting of themselves first and the process of their subjects, and this is our day to be achieved in all aspects of life.